Penatalaksanaan Fisioterapi dengan Shortwave Diathermy, Transcutaneous Electrical Nerve Stimulation, dan Terapi Latihan Hold Relax pada Osteoarthritis Knee Bilateral - Maharani Kintan Hermaningrum; Didik Purnomo (JURNAL RISET RUMPUN ILMU KEDOKTERAN, 2025)
Osteoarthritis is a degenerative joint disease whose exact cause is not yet fully understood. This condition is characterized by damage to the articular cartilage, resulting in pain, joint stiffness, decreased muscle strength, muscle spasms, and reduced functional activity of the patient. Several factors contribute to the development of osteoarthritis, including age, gender, race, genetic factors, smoking habits, history of trauma, type of occupation or physical activity, exercise habits, and obesity. The prevalence of osteoarthritis increases with age; among individuals aged 65–74 years, approximately 39% experience knee osteoarthritis and 23% experience hip osteoarthritis. In those over 70 years old, almost all individuals, both men and women, show symptoms of this condition. Osteoarthritis is a chronic progressive disease characterized by inflammation of the articular cartilage and synovial membrane, which causes persistent pain, joint stiffness, decreased muscle strength, and reduced mobility. Physiotherapy management for this condition aims to reduce pain, improve muscle strength, and enhance joint function. Common therapeutic modalities used include Shortwave Diathermy (SWD), Transcutaneous Electrical Nerve Stimulation (TENS), and the Hold Relax exercise technique, which helps relax muscles and increase joint range of motion